2022
DOI: 10.1186/s12909-022-03248-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the utility of virtual OSCE sessions as an educational tool: a national pilot study

Abstract: Background Objective Structured Clinical Examinations (OSCEs) are a common form of assessment used across medical schools in the UK to assess clinical competence and practical skills and are traditionally held in an in-person format. In the past, medical students have often prepared for such exams through in-person peer-assisted learning (PAL), however, due to the recent Covid-19 pandemic, many in-person teaching sessions transitioned to online-based formats. There is currently a paucity of res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Online teaching was a kind of shift that many pharmacy and medical schools targeted worldwide, especially after the COVID- (Grover et al, 2022) assessed the utility of virtual OSCE sessions as an educational tool in a national pilot study conducted among several universities in the UK. They concluded that V-OSCE workshops could act as a valuable learning resource that has the potential to be used even beyond the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Online teaching was a kind of shift that many pharmacy and medical schools targeted worldwide, especially after the COVID- (Grover et al, 2022) assessed the utility of virtual OSCE sessions as an educational tool in a national pilot study conducted among several universities in the UK. They concluded that V-OSCE workshops could act as a valuable learning resource that has the potential to be used even beyond the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a post OSCE survey for both students and the examiners depicted in [Supplementary document -5,6]. The survey used in our study was modi ed from the study published by (Grover et al, 2022).…”
Section: The Osce Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, many practical studies have been applied in education to investigate the unmet needs of students and to apply them to improve the educational field. Action research that measures and monitors the effectiveness of the educational curriculum development and application and revises education plans is a necessary process for improving educational efficiency and student satisfaction in the newly introduced education field [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%